1997
DOI: 10.1074/jbc.272.14.9573
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Human Zinc Finger Protein That Interacts with the Core Promoter Element of a TATA Box-less Gene

Abstract: We describe a novel human cDNA isolated by target site screening of a placental expression library, using as a probe, an essential element of a TATA box-less promoter corresponding to a pregnancy-specific glycoprotein gene. The cDNA encoded a predicted protein of 290 amino acids, designated core promoter-binding protein (CPBP), which has three zinc fingers (type Cys 2 -His 2 ) at the end of its C-terminal domain, a serine/threonine-rich central region and an acidic domain lying within the N-terminal region. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 33 publications
(37 reference statements)
5
106
0
Order By: Relevance
“…KLF6 mRNA is expressed at basal levels in most tissues and at relatively high levels in human and mice placenta (Koritschoner et al, 1997;Slavin et al, 1999). KLF6 protein expression is detected as two bands of 42 and 46 kDa in several tissues and cells lines (Kojima et al, 2000;Narla et al, 2001, this work) showing different intensity in Western blot assays probably reflecting differences in post-translational modifications.…”
Section: Klf6 Is a Phosphoprotein That Responds To Extracellular Stimulimentioning
confidence: 64%
See 3 more Smart Citations
“…KLF6 mRNA is expressed at basal levels in most tissues and at relatively high levels in human and mice placenta (Koritschoner et al, 1997;Slavin et al, 1999). KLF6 protein expression is detected as two bands of 42 and 46 kDa in several tissues and cells lines (Kojima et al, 2000;Narla et al, 2001, this work) showing different intensity in Western blot assays probably reflecting differences in post-translational modifications.…”
Section: Klf6 Is a Phosphoprotein That Responds To Extracellular Stimulimentioning
confidence: 64%
“…The cDNA encoding the complete open reading frame of KLF6 transcription factor (Koritschoner et al, 1997) was cloned into the pXJ, pSG424 and p513-HA expression plasmids to produce wtKLF6 or fused to Gal4-DNA-binding domain or to the hemmagglutinin epitope (HA), respectively (Sadowski et al, 1992). A version devoid of ZF 1-3 (DZF; amino acids 161-289) was also generated in pXJ and p513-HA (Chatton et al, 1995).…”
Section: Plasmids and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…We focused our present studies on the Kru Èppel-like zinc ®nger transcription factors (Ruppert et al 1988) which are a subset of the abundantly found DNA-binding C 2 H 2 -type zinc ®nger factors in eukaryotes (Klug & Schwabe 1995). Exempli®ed by the factors Sp1 (Dynan & Tjian 1983) and GBF (Suzuki et al 1998) (also known as CPBP (Koritschoner et al 1997) and Zf9 (Ratziu et al 1998) but hereafter referred to as GBF), they often bind GC-rich sequences with similar sequence-speci®c binding properties (Sogawa et al 1993;T. Suzuki & M. Horikoshi, unpublished results).…”
Section: Introductionmentioning
confidence: 99%